Dramaturgi Santri Nduduk di Lingkungan Pondok Pesantren Lirboyo - Asep Rahmatullah (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines the phenomenon of santri nduduk from a social dramaturgical perspective to understand how their identities, roles, and social interactions are formed and presented in pesantren life. The approach used is qualitative with a phenomenological study method through participatory observation, in-depth interviews, and documentation. The results of the study indicate that the practice of nduduk is not merely a physical activity of sitting or being in a certain space. Still, rather a symbolic arena for santri to build their self-image, demonstrate adherence to the ​​ pesantren’s values, and negotiate their social position before the kiai, ustaz, and fellow santri. Within the dramaturgical framework, the pesantren space functions as a front stage that demands an ideal appearance in accordance with religious norms, while the informal space serves as a back stage where santri can express themselves more freely. These findings confirm that pesantren culture forms a complex pattern of symbolic behavior in which religion, discipline, and power relations are intertwined in daily practice. This study is expected to make a conceptual contribution to the sociology of Islamic education, particularly by understanding the cultural dynamics and performativity of santri identity in the pesantren environment.